17, 18-Epoxyeicosatetraenoic Acid Inhibits TNF-α-Induced Inflammation in Cultured Human Airway Epithelium and LPS-Induced Murine Airway Inflammation. Issue 1 (January 2022) - Hara, Shiori; Tojima, Ichiro; Shimizu, Shino; Kouzaki, Hideaki; Shimizu, Takeshi
Background: 17, 18-Epoxyeicosatetraenoic acid (17, 18-EpETE), an eicosapentaenoic acid metabolite, is generated from dietary oil in the gut, and antiinflammatory activity of 17, 18-EpETE was recently reported. Objective: To evaluate the inhibitory effects of 17, 18-EpETE in airway inflammation, we examined in vitro and in vivo effects on mucus production, neutrophil infiltration, and cytokine/chemokine production in airway epithelium. Methods: Nasal tissue localization of G protein-coupled receptor 40 (GPR40), a receptor of 17, 18-EpETE, was determined by immunohistochemical staining. Expression of GPR40 mRNA in nasal mucosa of chronic rhinosinusitis (CRS) patients and control subjects was determined by reverse transcription-polymerase chain reaction (RT-PCR). The in vitro effects on airway epithelial cells were examined using normal human bronchial epithelial cells and NCI-H292 cells. To examine the in vivo effects of 17, 18-EpETE on airway inflammation, we induced goblet cell metaplasia, mucus production, and neutrophil infiltration in mouse nasal epithelium by intranasal lipopolysaccharide (LPS) instillation. Results: GPR40 is mainly expressed in human nasal epithelial cells and submucosal gland cells. RT-PCR analysis revealed that the expression of GPR40 mRNA was increased in nasal tissues from CRS patients compared with those from control subjects. 17, 18-EpETE significantly inhibited tumor necrosis factor (TNF)-α-induced production of interleukin (IL)-6, IL-8, and mucin from cultured human airway epithelial cells dose dependently, and these antiinflammatory effects on cytokine production were abolished by GW1100, a selective GPR40 antagonist. Intraperitoneal injection or intranasal instillation of 17, 18-EpETE significantly attenuated LPS-induced mucus production and neutrophil infiltration in mouse nasal epithelium. Inflammatory cytokine/chemokine production in lung tissues and bronchoalveolar lavage fluids was also inhibited. Conclusion: These results indicate that 17, 18-EpETE plays a regulatory role in mucus hypersecretion and neutrophil infiltration in nasal inflammation. Local or systemic administration may provide a new therapeutic approach for the treatment of intractable airway disease such as CRS.